Predictors of Coping Strategies among Cervical Cancer Patients at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia: A Cross-sectional Study - Dirar, Anteneh; Mekonnen, Wubegzier; Berhanu, Zena (Asian Pacific Journal of Cancer Care, 2022)
Background: The diagnosis and treatment of cervical cancer could result in psychological distress. Greater understanding of patients’ coping strategies, and influencing factors, can aid in developing appropriate psychosocial support. The aim of this study was to assess the prevalence of coping strategies and associated factors among cervical cancer patients. Materials and methods: A cross-sectional study was conducted among 299 cervical cancer patients on follow-up treatment at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia. Data were collected through face-to-face interview to assess patients’ sociodemographic characteristics, self-efficacy, meaning in life, perceived social support, uncertainty, cognitive appraisal, and coping strategies. Pearson’s correlation coefficient and linear regression analysis was conducted. Results: Findings reveal that women utilized both problem-focused and emotion-focused coping strategies. However, emotion-focused coping strategies were more frequently employed than problem-focused coping strategies by cervical cancer patients. Self-efficacy (ß=.27, p<.001), meaning in life-presence (ß= -.25, p=.015), perceived social support from friend (ß= .36, p<.001), and perceived social support from significant others (ß= -.27, p=.048) predicted emotion-focused coping strategies. Moreover, self-efficacy (ß=.25, p<.001), uncertainty (ß= -.13, p=.003), meaning in life-presence (ß= -.12, p=.003), meaning in life-search (ß= .12, p=.009), perceived social support from family (ß= .11, p=.021), and challenge appraisals (ß= .13, p=.010) were determinants of problem-focused coping strategies. Conclusion: This study demonstrates that women with cervical cancer adopt varied coping strategies to deal with their illness. Since coping strategies adopted are influenced by the extent of personal and environmental factors, there is a need to take these factors into account when developing tailored interventions to support patients’ coping strategies.